2012
DOI: 10.1111/j.1472-765x.2012.03223.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive stilbenes from a Bacillus sp. N strain associated with a novel rhabditid entomopathogenic nematode

Abstract: Aims:  The aim of the present study was to purify and characterize a natural antimicrobial compound from Bacillus sp. strain N associated with a novel rhabditid entomopathogenic nematode. Methods and Results:  The cell‐free culture filtrate of a bacterium associated with a novel entomopathogenic nematode (EPN), Rhabditis (Oscheius) sp. exhibited strong antimicrobial activity. The ethyl acetate extract of the bacterial culture filtrate was purified by column chromatography, and two bioactive compounds were isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Two stilbenes viz 3,4′,5-trihydroxystilbene and 3,5-dihydroxy-4-isopropylstilbene with antimicrobial activity were also isolated from the same bacterium associated with Rhabditis ( Oscheius ) sp. (Kumar et al 2012b ). Tryptophan containing diketopiperazines viz cyclo-( l -Trp- l -Pro), cyclo-( l -Trp- l -Tyr), cyclo-( l -Trp- l -Ile), cyclo-( l -Trp- l -Leu) and cyclo-( l -Trp- l -Phe) with antibacterial activity against human pathogenic bacteria were isolated from Comamonas testosteroni associated with R. ( Oscheius ) sp.…”
Section: Introductionmentioning
confidence: 99%
“…Two stilbenes viz 3,4′,5-trihydroxystilbene and 3,5-dihydroxy-4-isopropylstilbene with antimicrobial activity were also isolated from the same bacterium associated with Rhabditis ( Oscheius ) sp. (Kumar et al 2012b ). Tryptophan containing diketopiperazines viz cyclo-( l -Trp- l -Pro), cyclo-( l -Trp- l -Tyr), cyclo-( l -Trp- l -Ile), cyclo-( l -Trp- l -Leu) and cyclo-( l -Trp- l -Phe) with antibacterial activity against human pathogenic bacteria were isolated from Comamonas testosteroni associated with R. ( Oscheius ) sp.…”
Section: Introductionmentioning
confidence: 99%
“…It is a compound present in grape skins and wine, and is known to exhibit multi-spectrum therapeutic applications having been reported to exhibit anticancer, antiangiogenic, immunomodulatory, cardioprotective, and antioxidant activity. Although there is still very limited work on the antibacterial activity of resveratrol, it has been shown that resveratrol exhibits antibacterial activity against several Gram-positive and Gram-negative foodborne bacteria (Chan, 2002 ; Tegos et al, 2002 ; Paulo et al, 2010 ; Paolillo et al, 2011 ; Alvarez et al, 2012 , 2013 ; Kumar et al, 2012b ; Plumed-Ferrer et al, 2013 ; Augustine et al, 2014 ; Ferreira et al, 2014 ; Moran et al, 2014 ; Promgool et al, 2014 ; Subramanian et al, 2014 ; Duarte et al, 2015 ; Kim et al, 2015 ; Makwana et al, 2015 ; Ferreira and Domingues, 2016 ; Liu et al, 2016 ; Seukep et al, 2016 ; Silva et al, 2016 ; Surendran Nair et al, 2016 ; Klancnik et al, 2017 ; Lai et al, 2017 ; Lee and Lee, 2017 ; Oliveira et al, 2017 ). This review aims to provide an overview of the published data on the antibacterial activity of resveratrol against foodborne pathogens, its mechanisms of action as well as its possible applications in food packing and processing; in addition we also summarize the current data on its potential synergism with known antibacterials and future research and applications.…”
Section: Introductionmentioning
confidence: 99%
“…from Vitis vinifera, Shi et al 2012; Alternaria sp. from a mangrove plant Myoporum bontioides; Wang et al 2014b), emtomopathogenic bacteria (Photorhabdus luminescens, Eleftherianos et al 2007; Bacillus sp., Kumar et al 2012), several edible mushrooms (Peng et al 2015), sponge (Antarctic sponge Kirkpatrickia variolosa, Jayatilake and Baker 1995), and moth larva (dried silkworm larva of Bombyx mori, Kikuchi et al 2004). A recent transcriptome analysis provided the evidence at the gene level that stilbenes in the endophytic fungus Alternaria could be synthesized by CHS (Che et al 2016), and a recent structural analysis revealed that the stilbene 2-isoprpyl-5-[(E)-2-phenylvinyl] benzene-1,3-diol in bacteria Photorhabdus is synthesized by the collaboration of two enzymes, the unusual b-ketosynthase StlD and the aromatase StlC (Mori et al 2016).…”
Section: Stilbene Distribution Contents and Localizationmentioning
confidence: 99%